PENGEMBANGAN ALAT LATIHAN KETEPATAN SASARAN FOREHAND DRIVE PADACABANG OLAHRAGA TENIS LAPANGAN TAHUN 2021 - Frans Devin Tarigan; Amir Supriadi (Journal Physical Health Recreation (JPHR), 2021)
Tennis court is a small ball game. Playing tennis court is a sport that is almost the same as playing table tennis and badminton, having the same goal of hitting the ball over the net so that it reaches the opponent's area. The game of tennis court is played by one or a pair of players facing across the net. This research is aimed at developing forehand drive training aids in tennis athletes. Forehand drive training aids in tennis court are first validated by 6 experts, 2 material expert in sports, 2 expert in the field of equipment / media, 2 expert field coach. The results of the small group trial involved 3 experts, 1 material expert with an assessment result of 85%, 1 trainer expert 84% and 1 media expert 85% it can be concluded that they meet the criteria to be continued in large group trials. It can be concluded that the results of large group trials meet the criteria to be used in assisting forehand drive exercises in tennis court